Pengangguran, pendidikan, kesehatan, dan ketimpangan pendapatan terhadap kemiskinan di Indonesia - Aryanti, Ema Dwi; Sukardi, Agung Slamet (Nur Science Institute, 2024)
The problem of poverty occurs in all developed and developing countries. So does Indonesia, where this problem has also hit. This research was conducted to determine the influence of unemployment, education, health, and income inequality on poverty in Indonesia in 2013-2022. Secondary data from Statistics Indonesia is used in this research. Sampling in this study used saturated samples. The data analysis techniques used in multiple linear regression research. The analysis found that unemployment and education did not affect the rise and fall of poverty levels in Indonesia. Meanwhile, other results show that health variables influence the poverty level in a negative direction. Meanwhile, income inequality between regions and between populations influences the poverty level in a positive direction.